(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Producing bacteria (LAB) from FRUITS AND VEGETABLE WASTE have been identified. It wasdiscovered that these microorganisms were capable of producing the antibiotic bacteriocin.Lactobacillus lactis Lactobacillus plantarum were the most effective makers of bacteriocins among theisolated cultures. A wide range of food spoilage germs and related strains of LAB were inhibited bybacteriocin generated by these Lactobacillus species. Escherichia coli was suppressed by thebacteriocin, but Candida albicans was the only organism it had any effect on. Between the latelogarithmic phase or the early stationary phase, the antibacterial activity seemed to be most strong. Ithas been discovered that the bacteriocins are heat-resistant. Lactose, peptone, and yeast extract wereadded to boost bacteriocin synthesis.